2017
DOI: 10.37358/rc.17.1.5417
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Nanofillers on Composite Materials Mechanical Properties

Abstract: The goal study is benchmarking flexural strength FS of compressive strength CS, compression diametrical DTS (diametrically tensile strenght) and Vickers hardness for two nanocomposites experimental AD1 and AD3 achieved within the Research Institute in Chemistry Raluca Ripan Cluj Napoca and for the commercial product of the Kerr Premise company �. Electron microscopy aspects pre- and post-fracturing are also shown to highlight the structure of materials and spread

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…After adding the nanoclay beyond the optimum level, in this case at 10 wt%, the d-spacing of nanoclay tends to reduce, attributed to the overloading of nanoclay and thus a closer distance between the silicate plates. This phenomenon is often ascribed to the effect of reagglomeration of nanoclays [25,47,48]. As expected, the organo-nanoclay is, to some extent, compatible with the isoprene monomer.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…After adding the nanoclay beyond the optimum level, in this case at 10 wt%, the d-spacing of nanoclay tends to reduce, attributed to the overloading of nanoclay and thus a closer distance between the silicate plates. This phenomenon is often ascribed to the effect of reagglomeration of nanoclays [25,47,48]. As expected, the organo-nanoclay is, to some extent, compatible with the isoprene monomer.…”
Section: Resultsmentioning
confidence: 60%
“…In order to make nanofillers well-dispersed in a rubber matrix, the researchers in this field have paid close attention to many aspects of the particular composites. These include: studies concerning intrinsic properties of raw materials in the composites, e.g., the modifications of polymers [19,20], fillers [21,22], and processing aids [23,24]; novel syntheses of key materials for the composites [25,26,27]; and the optimizations of different processing techniques and conditions, e.g., melt [28,29] and solution [30,31] mixing, mixing time and temperature, mixing procedure, pre-dispersion methods, etc., [32,33]. This technology remains challenging since the properties of a composite depend strongly on the processing conditions as well as composition.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study the composite resin having higher amounts of the fillers showed better mechanical results. Other studies also demonstrated this correlation [18]. A possible explanation for this condition might be due to the fact that smaller particles size are related to a higher filler content by volume and a better distribution of the filler.…”
Section: Resultsmentioning
confidence: 63%
“…The properties of composites are influenced by type and extent of filler and inorganic silane and correct distribution of nanoparticles in the organic phase. In vitro studies are necessary to evaluate the biocompatibility of all dental materials [29][30][31].…”
Section: Figurementioning
confidence: 99%